A model of a tacit knowledge transformation for the service department in a manufacturing company: A case study - Adam Dudek; Justyna Patalas-Maliszewska (Foundations of Management, 2016)
This article elaborates on the development of a dedicated model of a tacit knowledge transformation for the service department in a manufacturing company. The four main components of the tacit knowledge transformation process are formulated: (1) tacit knowledge source identification, (2) tacit knowledge acquisition, (3) tacit knowledge determination and formalization, and (4) knowledge classification. The proposed model is illustrated by examples on the use of the methods: automatic recognition of speech, natural language processing, and automatic object recognition in the tacit knowledge transformation process in order to obtain a formalized procedure for the service department in a manufacturing company. This is followed by a discussion of the results of the research experiments.
Keywords: 650; case study; tacit knowledge transformation process; automatic recognition of spoken; natural language processing; automatic object recognition; manufacturing company